Stages of breast reconstruction and quality of life after breast cancer - Murici, Aline Fernanda Fontinele; Barros, Ângela Ferreira (Mastology, 2020)
Objective: To evaluate which stage of breast reconstruction promotes improved quality of life for women treated for breast cancer, and to verify the socioeconomic and clinical factors associated with better quality of life. M ethods: A cross-sectional study was conducted with 70 women treated for breast cancer in the perioperative period of late breast reconstruction in the Federal District. To assess quality of life, the Functional Assessment of Cancer Therapy — Breast (FACT-B) instrument was used. Results: Half of the women were under 50 years old. Tumor removal surgery had occurred on average 5.4 years ago. Women with axillary dissection had greater impairment in the physical well-being domain (p=0.001) and the breast cancer subscale (p=0.016). Among women who had undergone surgery more than one year previously, there were higher domains of emotional (p=0.006) and functional (p=0.003) well-being. Women who underwent breast reconstruction had higher values in the social/family well-being (p<0.001), emotional well-being (p=0.001), functional well-being (p=0.001), and breast cancer subscale (p=0.005) domains; and on the FACT-B score (p<0.001), right after the first stage. Conclusions: Breast reconstruction favored better quality of life from the first stage, suggesting that this therapeutic modality should be offered promptly, whenever possible, and guaranteed for all women treated for breast cancer.